Husband's Support and Knowledge about Birth with Anxiety Facing Primigravida Birth - Hafsa, Andi; Suroso, Suroso; Titi Pratitis, Niken (Riviera Publishing, 2024)
This study aims to investigate the relationship between husbands' support and knowledge regarding childbirth and the level of anxiety experienced by primigravida during the childbirth process. The research adopts a quantitative approach by analyzing data from 297 pregnant women who visited during the months of March-April 2023. The analytical method employed is Multiple Linear Regression Analysis using SPSS version 25. The research findings reveal a highly significant correlation between husbands' support and knowledge together with the anxiety levels experienced by primigravida. The implications of these findings provide further insight into the importance of the husband's role in providing support and knowledge to their partners during pregnancy and childbirth. Moreover, this research lays the groundwork for the development of interventions aimed at reducing the anxiety levels of primigravida through the enhancement of husbands' support and knowledge. Practical implications of this study include the development of reproductive health education programs that focus more on involving husbands in supporting the mental and emotional well-being of pregnant women.